Neuropsychological evaluation of inhibitory control and interference control: Validation of experimental tasks in the ecuadorian context - Ramos Galarza, Carlos; Jadán Guerrero, Janio; Ramos D.; Bolaños M.; Ramos V.; Fiallo-Karolys M.X. (My University, 2017)
This article reports a study in which three experimental tasks (SIMON, Go / No-Go and Stroop Victoria) were adapted and validated to evaluate the inhibitory control and interference control in a sample of Ecuadorian students. The sample consisted of 100 students between 6 and 15 years old (M = 10.13 years, SD = 2.48) belonging to the public education system of Ecuador. The process followed in the adaptation and validation was through the linguistic translation of the experiments, followed by an expert judgment and a pilot study. In the results it was found that there are no statistically significant differences in the measures that assess the inhibitory control and the interference considering the sociodemographic variables of the participants as comparison factors. In the correlation analysis we found a statistically significant association between the measurements of the experiments. We conclude by analyzing the associations found and underlining the need to continue providing evidence in the research line of adaptation and validation of test for using in neuropsychological evaluation.
Keywords: Neuropsychological evaluation; Neuropsychological rehabilitation; Neuroscience; Theoretical development of the study of the human brain